UV-cured wind power blade repair resin and preparation method thereof

Through UV curing wind power blade repair resin system, combining the mixture of epoxy resin and acrylate resin, the problem of insufficient curing depth of wind power blade repair materials in low temperature environments is solved, and efficient repair is achieved at -20℃ without heating. Provides high mechanical strength and corrosion resistance.

CN119220052APending Publication Date: 2024-12-31YANTAI DONGHUA MATERIAL SCI CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411337207.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing wind power blade repair materials have insufficient curing depth in low temperature environments and require heating or solvents, which cannot meet the winter repair needs of northern wind farms, especially in the harsh conditions of -20℃.

Method used

UV cured wind power blade repair resin system is adopted, and through the mixing of epoxy resin and acrylate resin, combined with photothermal cation system and photoradical system, rapid curing at room temperature is achieved, heating and solvents are avoided, and high mechanical strength and corrosion resistance are provided.

Benefits of technology

It realizes rapid molding and high mechanical strength repair at -20℃, has good adhesive strength, strong corrosion resistance, and no surface oxygen resistance during curing. It is suitable for wind power blade repair in low-temperature environments, reducing maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of composite prepreg, and relates to UV curing wind power blade repairing resin and a preparation method thereof.The repairing resin comprises a component A and a component B. The component A comprises, by weight, 0-60 parts of glycidyl epoxy resin, 30-80 parts of alicyclic epoxy resin, 0-20 parts of oxetane and 2-30 parts of flexibilizer; the component B is prepared from the following components in parts by weight: 90 to 99 parts of olefin monomer or olefin resin, 0.1 to 6 parts of free radical photoinitiator, 0.1 to 2 parts of thermal cationic initiator and 0.1 to 5 parts of photo cationic initiator. The UV-cured wind power blade repair resin is a hybrid system of an epoxy resin system and acrylate resin, has the advantages of light curing of epoxy resin and acrylate resin, does not need heating or solvent, is controllable in reaction degree, can be quickly formed at low temperature, and has the repair thickness gt; and the material can be applied to repair in winter and other severe environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material prepregs, and in particular relates to a UV-curing wind turbine blade repair resin and a preparation method thereof. Background Art

[0002] Wind turbine blades are one of the key components of wind power generation, accounting for a large proportion of the total machine cost. After being put into operation, they need to withstand the test of operation for more than 15 years. Under ideal environment and reliable operating conditions, wind turbine blades have a design life of 20 years. However, in the actual operating environment, the blades are eroded by various media in the air, and lightning, hail, rain, snow, sand and dust, and alternating high and low temperatures also cause damage to the blades. In addition, the hidden dangers caused by improper operation or other human factors during the transportation, installation and operation of the blades may evolve into accidents at any time.

[0003] The main structure of the blade is a fiberglass composite material, and its biggest feature is its repairability. Maintaining the initial problems found on the blade can avoid high maintenance costs in the future and reduce economic losses caused by downtime. Therefore, the selection of blade repair resin system is particularly critical. Ordinary blades are epoxy resin hand-layup systems. Although they have good strength, they must be cured at above 70°C to fully exert their mechanical properties; although the vinyl resin system can react at room temperature, the curing time is extremely long and the repair efficiency is low. For the current low temperature conditions (such as -20°C) in my country's northern wind farms, a resin system with both high enough mechanical strength and simple and fast curing is needed to solve the repair problem in harsh environments. At present, Gurit has developed UV-cured RENUVO repair materials for blade maintenance, which have passed GL certification. The product can be used at temperatures as low as 5°C, but it cannot meet the winter repair requirements of my country's northern wind farms. The UV-cured epoxy resin on the market has a poor curing depth and a large viscosity, and cannot be used for wind turbine blade repair at -20°C.

[0004] In summary, the wind turbine blade repair industry needs a new type of high-quality light-curing repair resin that does not require heating or solvents and can be quickly molded at -20°C. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a UV-curable wind turbine blade repair resin and a preparation method thereof. The specific technical scheme is as follows:

[0006] The first object of the present invention is to provide a UV curing wind turbine blade repair resin, comprising component A and component B, which are calculated by weight.

[0007] Component A includes:

[0008] 0-60 parts of glycidyl epoxy resin, 30-80 parts of alicyclic epoxy resin, 0-20 parts of oxetane, 2-30 parts of toughening agent;

[0009] Component B includes:

[0010] 90-99 parts of olefin monomer or olefin resin, 0.1-6 parts of free radical photoinitiator, 0.1-2 parts of thermal cationic initiator, 0.1-5 parts of photocationic initiator;

[0011] The mass ratio of the component A to the component B is 100:20-50.

[0012] The UV-curable wind turbine blade repair resin provided by the present invention is a mixed system of epoxy resin system and acrylate resin. It adopts the synergistic effect of epoxy resin-photothermal cation system and vinyl resin-photoradical system, and has the advantages of epoxy resin and acrylate resin photocuring. There is no surface oxygen inhibition for curing, and it can be cured in a sub-zero environment. It is a low-viscosity liquid resin at room temperature, and can infiltrate reinforcing fibers without adding solvents or heating. Under the action of UV radiation, it reacts in a short time to complete pre-curing to form a reinforcement system. The photoinitiator decomposes under the action of light to initiate the curing of epoxy resin and acrylate. The heat released during the curing process triggers the decomposition of cations to produce proton acid. The proton acid attacks the epoxy monomer to initiate cationic ring-opening polymerization, and then performs post-curing. The shrinkage rate of the curing process is small, the mechanical strength after curing is excellent, the Tg is controllable, the adhesion is good, and the corrosion resistance is good.

[0013] Furthermore, the glycidyl epoxy resin is one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, and phenolic epoxy resin.

[0014] The glycidyl ether epoxy resin can improve flexibility and reduce cost, the glycidyl ester epoxy resin can improve low temperature toughness, and the glycidyl amine epoxy resin and the phenolic epoxy resin can improve corrosion resistance.

[0015] Furthermore, the alicyclic epoxy resin is one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, 3,4-epoxycyclohexyl methyl methacrylate, and epoxy soybean oil acrylate.

[0016] Furthermore, the oxetane is one or both of 3-ethyl-3-epoxypropylene methanol and 3,3-(oxybismethylene)bis(3-ethyl)oxetane.

[0017] Furthermore, the toughening agent is one or more of polyether polyols, polyester polyols, aliphatic diols, and polyols, preferably one or more of 1,2-ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, 3-ethyl-3-epoxypropylene methanol, PEG400, PPG400, polytetramethylene glycol, polycaprolactone polyol, and polycarbonate polyol.

[0018] Furthermore, the olefin monomer or olefin resin is one or more of acrylic acid, acrylic acid ester, methacrylic acid ester, vinyl resin, and vinyl ether, preferably one or more of acrylic acid, hydroxybutyl acrylate, diethylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, dipropylene glycol dimethacrylate, and glycidyl methacrylate.

[0019] Furthermore, the free radical photoinitiator is one or more of 184, 1173, 907, 819, 754, 369, ITX, MBF, BDK, and TPO.

[0020] Furthermore, the thermal cationic initiator is one or more of hexafluoroantimonate, hexafluorophosphate, and trifluoromethanesulfonate type thermal initiator cationic curing agents.

[0021] Furthermore, the photocationic initiator is one or both of sulfonium salt and iodonium salt.

[0022] The second object of the present invention is to provide a method for preparing the above-mentioned UV-curable wind turbine blade repair resin, comprising the following steps:

[0023] (1) Preparation of component A: Add glycidyl epoxy resin, alicyclic epoxy resin, oxetane and toughening agent into a sealed reactor, stir and disperse at 30-50° C., 500-1000 r / min for 0.5-1 h, then stir in vacuum for 0.5-1 h, cool to room temperature while stirring in vacuum, and pour into a black container and seal for storage;

[0024] (2) Preparation of component B: Add olefin monomer or olefin resin into a sealed reactor, and then add free radical photoinitiator, thermal cationic initiator, and photocationic initiator in a light-proof state; mechanically stir and disperse at 500-1000 r / min for 0.5-1 h at 25-35° C., then vacuum stir for 0.5-1 h, and cool to room temperature while vacuum stirring. Pour into a black container and seal for storage.

[0025] (3) Preparation of mixed formula: Mix component A and component B according to the mass ratio and stir them in vacuum at 20-35°C for 0.5-1h to obtain the mixed formula.

[0026] When in use, the fiber is fully soaked in the above-mentioned UV curing wind turbine blade repair resin and attached to the polished notch on the wind turbine blade. The wavelength is 365nm and the power is 700-1500mW / cm 2 The blades can be reinforced and the wind turbine blades can be repaired by curing with UV light for 6 to 15 minutes.

[0027] The beneficial effects of the present invention are:

[0028] The present invention has developed a new type of UV radiation light-curing repair resin, which does not require heating or solvents, has a controllable reaction degree, can be quickly formed at low temperatures, and has a repair thickness of >4mm. The resin is still a low-viscosity liquid resin in a harsh environment of -20°C, and can still be used to impregnate reinforcing fibers in a harsh environment of -20°C. Under the action of UV radiation, it reacts in a short time to complete the curing, thereby achieving blade reinforcement and completing wind turbine blade repair. In addition, it maintains the same or higher positive properties as known systems, such as Tg>70°C, excellent mechanical strength, and lower mixed viscosity. Component A and component B of the present invention can also be mixed together as a single component and stably stored at low temperature (<-5°C) for 3 months. DETAILED DESCRIPTION

[0029] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0030] Example 1

[0031] A preparation method of a UV-curable wind turbine blade repair resin comprises the following steps:

[0032] (1) Preparation of component A: 40 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester (Nantong Synasia New Materials Co., Ltd., S-06E), 40 parts of bisphenol A epoxy resin, 10 parts of 3-ethyl-3-epoxypropane methanol (Nantong Synasia New Materials Co., Ltd., S-101), and 10 parts of PPG400 were dispersed at 40°C, 500 r / min for 0.5 h, and then vacuum stirred for 0.5 h, and cooled to room temperature;

[0033] (2) Preparation of component B: 97.5 parts of tripropylene glycol diacrylate, 2 parts of TPO initiator, 0.5 parts of hexafluoroantimonate thermal cationic curing agent, and 1 part of photocationic initiator 6976 (sulfonium salt) were dispersed under mechanical stirring at 25°C and 500 r / min for 0.5 h in a light-proof state, and then cooled to room temperature;

[0034] (3) Preparation of mixed formula: 100 parts of component A and 30 parts of component B were stirred under vacuum at 25°C for 0.5 h to obtain the final resin.

[0035] Example 2

[0036] A preparation method of a UV-curable wind turbine blade repair resin comprises the following steps:

[0037] (1) Preparation of component A: 40 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester (Nantong Synasia New Materials Co., Ltd., S-06E), 40 parts of bisphenol A epoxy resin, 10 parts of 3-ethyl-3-epoxypropane methanol (Nantong Synasia New Materials Co., Ltd., S-101), and 10 parts of PPG400 were dispersed at 40°C, 500 r / min for 0.5 h, and then vacuum stirred for 0.5 h, and cooled to room temperature;

[0038] (2) Preparation of component B: 97.3 parts of tripropylene glycol diacrylate, 3 parts of TPO initiator, 0.7 parts of hexafluoroantimonate thermal cationic curing agent, and 2 parts of photocationic initiator 6976 (sulfonium salt) were dispersed under mechanical stirring at 25°C and 500 r / min for 0.5 h in a light-proof state, and then cooled to room temperature;

[0039] (3) Preparation of mixed formula: 100 parts of component A and 30 parts of component B were stirred under vacuum at 25°C for 0.5 h to obtain the final resin.

[0040] Example 3

[0041] A preparation method of a UV-curable wind turbine blade repair resin comprises the following steps:

[0042] (1) Preparation of component A: 80 parts of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester (Nantong Synasia New Materials Co., Ltd., S-06E), 10 parts of PPG400, and 10 parts of 1,4-butanediol were dispersed at 40°C, 500 r / min for 0.5 h, and then vacuum stirred for 0.5 h, and cooled to room temperature;

[0043] (2) Preparation of component B: 97.5 parts of dipropylene glycol diacrylate, 2 parts of TPO-L initiator, 0.5 parts of trifluoromethanesulfonate thermal cationic curing agent, and 2 parts of photocationic initiator 6976 (sulfonium salt) were dispersed under light-proof conditions at 25°C and 500 r / min with mechanical stirring for 0.5 h, and then cooled to room temperature;

[0044] (3) Preparation of mixed formula: 100 parts of component A and 50 parts of component B were stirred under vacuum at 25°C for 0.5 h to obtain the final resin.

[0045] After the formula material is prepared according to the above embodiment, it is cast into mechanical splines, using a wavelength of 365nm and a power of 1000mW / cm 2 The film was irradiated with UV light for 15 minutes for light curing.

[0046] Comparative Example 1

[0047] 90 parts of bisphenol A epoxy resin, 10 parts of 1,4-butanediol diglycidyl ether, and 35 parts of polyetheramine D230 were stirred and mixed at a speed of 500-1000 rpm to obtain a hand-paste resin for wind turbine blades;

[0048] After the formula material was prepared according to the comparative example 1, it was cast into mechanical specimens and post-cured at 75° C.×4 h.

[0049] Performance test standards

[0050] (1) Viscosity: BS EN ISO3219:1995;

[0051] (2) Tensile and bending properties: GB / T 2567-2008;

[0052] (3) Glass transition temperature (Tg): IEC 61006;

[0053] The mechanical properties and thermal properties of the cured product were evaluated. The specific evaluation results are as follows:

[0054] Table 1 Performance test results of the cured products of the embodiments and comparative examples

[0055]

[0056]

[0057] From the experimental results, it can be seen that the UV-curing wind turbine blade repair resin prepared by the present invention has extremely low viscosity, which is conducive to the infiltration of fibers; and the preparation method is simple, without the need for solvent treatment, and the overall performance after photocuring is basically the same as the resin performance of the commercialized hand-layup repair system in Comparative Example 1, and the UV-curing wind turbine blade repair resin prepared by the present invention can be used for repairs in winter and other harsh environments.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A UV curing wind turbine blade repair resin, characterized in that: Including component A and component B, by weight, Component A includes: 0-60 parts of glycidyl epoxy resin, 30-80 parts of alicyclic epoxy resin, 0-20 parts of oxetane, 2-30 parts of toughening agent; Component B includes: 90-99 parts of olefin monomer or olefin resin, 0.1-6 parts of free radical photoinitiator, 0.1-2 parts of thermal cationic initiator, 0.1-5 parts of photocationic initiator; The mass ratio of the component A to the component B is 100:20-50.

2. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The glycidyl epoxy resin is one or more of glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin and phenolic epoxy resin.

3. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The alicyclic epoxy resin is one or more of 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, 3,4-epoxycyclohexyl methyl methacrylate, and epoxy soybean oil acrylate.

4. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The oxetane is one or two of 3-ethyl-3-epoxypropylene methanol and 3,3-(oxybismethylene)bis(3-ethyl)oxetane.

5. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The toughening agent is one or more of polyether polyol, polyester polyol, aliphatic diol and polyol.

6. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The olefin monomer or olefin resin is one or more of acrylic acid, acrylic acid ester, methacrylic acid ester, vinyl resin, and vinyl ether.

7. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The free radical photoinitiator is one or more of 184, 1173, 907, 819, 754, 369, ITX, MBF, BDK, and TPO.

8. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The thermal cationic initiator is one or more of hexafluoroantimonate, hexafluorophosphate, and trifluoromethanesulfonate type thermal initiator cationic curing agents.

9. The UV curing wind turbine blade repair resin according to claim 1, characterized in that: The photocationic initiator is one or both of sulfonium salt and iodonium salt.

10. A method for preparing a UV-curable wind turbine blade repair resin according to any one of claims 1 to 9, characterized in that: The steps include: (1) Preparation of component A: Add glycidyl epoxy resin, alicyclic epoxy resin, oxetane and toughening agent into a sealed reactor, stir and disperse at 30-50° C., 500-1000 r / min for 0.5-1 h, then stir in vacuum for 0.5-1 h, cool to room temperature while stirring in vacuum, and pour into a black container and seal for storage; (2) Preparation of component B: Add olefin monomer or olefin resin into a sealed reactor, and then add free radical photoinitiator, thermal cationic initiator, and photocationic initiator in a light-proof state; mechanically stir and disperse at 500-1000 r / min for 0.5-1 h at 25-35° C., then vacuum stir for 0.5-1 h, and cool to room temperature while vacuum stirring. Pour into a black container and seal for storage. (3) Preparation of mixed formula material: Component A and component B are mixed according to the mass ratio and stirred in vacuum at 20-35° C. for 0.5-1 h to obtain the UV-curable wind turbine blade repair resin.

Citation Information

Cited By

  • Photocuring hand lay-up resin system for low-temperature environment in winter and preparation method of photocuring hand lay-up resin system

    CN120025501A

  • Dual-curing front-line polymer resin system for repairing fan blade and preparation method of dual-curing front-line polymer resin system

    CN120349477A

  • Photo-thermal curing epoxy resin composition for repairing thick layer and preparation method of photo-thermal curing epoxy resin composition

    CN122060382A